2020
DOI: 10.1186/s13027-020-00323-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel concepts in cervical cancer screening: a comparison of VIA, HPV DNA test and p16INK4a/Ki-67 dual stain cytology in Western Kenya

Abstract: Background Screening of unvaccinated women remains essential to mitigate the high morbidity/mortality of cervical cancer. Here, we compared visual inspection with acetic acid (VIA), recommended by WHO as the most cost-effective screening approach in LMICs, with HPV-based screening, and usage of p16INK4a/Ki-67 dual stain cytology. Methods We prospectively enrolled women participating in a VIA-based cervical cancer screening program in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 77 publications
(103 reference statements)
0
12
0
Order By: Relevance
“…For the above, we proposed a panel of three cellular biomarkers (TOP2A/MCM2, p16 INK4a , and cyclin-E), which, according to the statistical analysis and their function, are the most useful for evaluating the exacerbated proliferative activity of cervical cells, which is one of the earliest hallmarks of carcinogenesis. Other studies also indicated the usefulness of a biomarkers panel, based on the dual detection of p16 INK4a /Ki-67 for the screening of cervical lesions induced by HPV [ 13 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the above, we proposed a panel of three cellular biomarkers (TOP2A/MCM2, p16 INK4a , and cyclin-E), which, according to the statistical analysis and their function, are the most useful for evaluating the exacerbated proliferative activity of cervical cells, which is one of the earliest hallmarks of carcinogenesis. Other studies also indicated the usefulness of a biomarkers panel, based on the dual detection of p16 INK4a /Ki-67 for the screening of cervical lesions induced by HPV [ 13 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have recommended the implementation of p16/Ki-67 and HPV-DNA tests combination for safe monitoring the recurrence of CIN2+ given that some patients treated for CIN2 and CIN3 tend to relapse overtime [28]. However, there is a serious doubt as to whether a combination p16/Ki-67 assay and VIA may serve as alternative in facilities with resource limitations considering low sensitivity associated with VIA [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies conducted in Latin America, Asian and African countries, among the general female population reported that the VIA test positivity was 7.1%, 6 9.7%, 8 7.6%, 16 6.6%-16.1%, 26 5.5%-34.4%, 27 6.0%, 28 and 7.0%. 7 Similar studies conducted in Ethiopia among eligible women in the general population also showed varied results. For instance, in Butajira, test positivity of VIA was low (4.7%), 10 and in Jimma, VIA positive result was 12.9%.…”
Section: Discussionmentioning
confidence: 93%